A Quasi-dimensional Model of the Ignition Delay for Combustion Modeling in Spark-Ignition Engines - Grasreiner, Sebastian; Neumann, Jens; Wensing, Michael; Hasse, Christian (Journal of Engineering For Gas Turbines and Power-Transactions of the Asme, 2015)
Quasi-dimensional (QD) modeling of combustion in spark-ignition (SI) engines allows to describe the most relevant processes of heat release. Here, a submodel for the ignition delay is introduced and applied. The start of combustion is considered from ignition to the crank angle of 5% burned gas fraction. The introduced physical approach identifies the turbulent propagation velocity of the initiated kernel by taking into account early flame expansion and geometric restrictions of the flame propagation. The model is applied to stationary operation within an entire engine map of a turbocharged direct injection SI engine with fully variable valvetrain. Based on provided cycle-averaged input data, the model delivers good results within the margins of measured cycle-to-cycle fluctuations. Thus, it contributes to the assessment of the interplay between engine, engine control unit, drivetrain, and vehicle dynamics, hence making a step toward optimization and virtual engine calibration.
Created from Fastlane, Scopus look-up